Kepatuhan Wajib Pajak Badan Selama Era Pandemi Covid 19: Insentif Pajak, Sosialisasi Perpajakan dan Kesadaran Wajib Pajak - Welvin I Guna; Santi Amalya Amini; Amrie Firmansyah; Estralita Trisnawati (JURNAL PAJAK INDONESIA, 2022)
This study examines the effect of tax incentives, tax socialization, and awareness of taxpayers on corporate taxpayer compliance. This research is a quantitative study using primary data sourced from questionnaires to respondents. As for the criteria for respondents in this study, the minimum is supervisors related to corporate tax. The number of samples in this study is 35 observations based on purposive sampling. The results of this study indicate that tax incentives and socialization do not affect corporate taxpayer compliance, while taxpayer awareness has a positive effect on corporate taxpayer compliance. This research indicates that the tax authorities in Indonesia need to improve policies related to the provision of tax incentives and socialization to increase government tax revenues.